Psychological impact of COVID-19 pandemic among healthcare workers in Paraguay: A descriptive and preliminary study - Villalba-Arias, Jorge; Estigarribia, Gladys; Bogado, José Andrés; Méndez, Julieta; Toledo, Santiago; González, Israel; Castaldelli-Maia, João Mauricio; Ventriglio, Antonio; Torales, Julio (Medicina Clínica y Social, 2020)
Introduction: Healthcare workers exposed to SARS-CoV-2 are vulnerable to psychological distress. The goal of this study is to evaluate the psychological impact of exposure to the SARS-CoV-2 among healthcare workers in Paraguay. Methodology: A descriptive cross-sectional study was carried out in 5 tertiary hospitals in the Central, San Pedro and Caaguazú Departments of Paraguay during the COVID-19 pandemic from April to June 2020. The pilot study included 125 healthcare workers as participants, 25 for each hospital. Demographic data and occupational exposure data were collected with an ad-hoc questionnaire. Symptoms of depression and anxiety were evaluated employing the Patient Health Questionnaire-9, and the Generalized Anxiety Disorder scale-7. The prevalence of post-traumatic stress was determined using the Post-Traumatic Stress Disorder Check List-C. Results: Of the 125 participants, 68 (54.8%) were doctors, 37 (29.8) nurses, 7 (5.6%) biochemists, 3 (2.4%) obstetricians, and 9 (7.3%) other healthcare workers. Most participants were females (86 [68.8%]), with an average age of 33.8 years (SD ± 7.4), single (71 [56.8%]), with a postgraduate educational level (83 [66.4%]), and reporting a junior level of work experience (52 [41.6%]). A total of 71 (57.3%) were classified as high-risk healthcare workers after exposure to SARS-CoV-2. 61 (48.8%) of participants presented symptoms of depression, and 68 (54.4%) presented symptoms of anxiety. A small group reported symptoms of post-traumatic stress (9 [7.2%]). Conclusion: Healthcare workers in Paraguay reported a significant prevalence of depressive and anxious symptoms during the COVID-19 pandemic. These findings lend support to the idea that healthcare workers are vulnerable to psychological distress and that they may require specific mental health interventions.
Keywords: Healthcare workers; mental health; COVID-19; anxiety; depression; post-traumatic stress; psychological distress